Educational Film Screening : Meningkatkan Moralitas dan kepedulian akan Hak Azasi Manusia (HAM) - Sari, Nurvica (Universitas Klabat, 2022)
In today's modern era where most people are racing in the development of technology and innovation, the ability to hone conscience and morals is no longer a priority in everyday life. Many people only care about personal needs and interests without paying attention to good norms or values. As a result, individuals become selfish creatures and are not sensitive to the value of conscience and morals. Traditional culture and values seem to have been eroded by the times. Not only that, the sense of concern for human rights also seems to fade, where when there are other individuals or groups who are persecuted, conscience does not beat to help or provide support or even care. Therefore, this community service activity is carried out to hone conscience and morals among the younger generation of the nation's successors so that later morality and concern will be honed again and conscience and morals will beat again.